Administrative Burden at the Information and Communication Technology Development Center (BPTIK) of the Culture and Education Service (Dikbud) of Central Java Province, Indonesia - Putri Amboro, Jovinka Aprilian; Selvia Dewi Maharani (Arkus, 2024)
This article discusses the administrative burden at the Information and Communication Technology Development Center (BPTIK) of the Culture and Education Service (Dikbud) of Central Java Province. BPTIK has broad responsibilities in the development and use of information and communication technology (ICT) in the education sector. The main focus of the article is the dynamics of administration at BPTIK Dikbud Central Java Province, with an emphasis on the challenges, management, and potential for improving the administrative framework in the ICT domain. The aim of this research is to examine, confirm and understand aspects related to the administrative burden faced by BPTIK Dikbud Central Java Province. This article provides highlights on duties, authority, and obstacles in their implementation. Through a normative juridical approach and qualitative data collection, this research includes analysis of organizational characteristics, number of personnel, organizational structure, and ongoing administrative procedures. The research results identified several solutions and steps to increase productivity and optimize the management of administrative burdens at BPTIK Dikbud Central Java Province. These suggestions involve the use of technology, implementation of clear standards and procedures, training and coaching employee performance, as well as regular evaluation and supervision. In evaluating the impact of administrative burden, this article notes both positive and negative impacts. Utilization of ICT as a tool in administration can increase efficiency, quality and collaboration. However, high administrative burdens can also cause stress and hinder ICT development and innovation in institutions. Thus, the author recommends good management, adoption of appropriate technology, implementation of standards, employee training, and strong collaboration with related parties as strategic steps to manage the administrative burden at BPTIK Dikbud Central Java Province.